Twin wire arc spray 공정을 통해 제작된 Fe계 비정질 합금 코팅의 염수 환경 노출에 대한 연구 - 권한솔; Hansol Kwon; 강용진; Yongjin Kang; 유연우; Yeonwoo Yoo; 김도현; Dohyeon Kim; 박영진; Youngjin Park; 남욱희; Uk Hee Nam; et al. (대한금속·재료학회지, 62(8), 2024)
Fe-based amorphous alloys are promising structural materials that have a disordered lattice structure and metastable state. Due to their advanced properties, including high hardness, high elastic limit, improved wear and corrosion resistance, Fe-based amorphous alloys have a great potential for protective materials in harsh industrial fields. Twin wire arc spray (TWAS), which is a kind of thermal spray process, is a reasonable choice for depositing Fe-based amorphous coating. Industrial advantages of TWAS include simple apparatus, low cost, excellent field usability. Several previous studies of TWAS Fe-based amorphous coating have reported microstructural features, the effect of major element variation, and the effect of postheat treatment. Unfortunately, studies about Fe-based amorphous coating exposed to soluble salt solution are limited. Thus, a Fe-based amorphous coating was fabricated using TWAS in this study, and the effect of 3.5 wt.% NaCl solution exposure on its microstructure and mechanical properties was researched. Single- and multi-layer coatings were fabricated and Al-3%Ti was selected as a bond coat material. The results showed that single- and multi-layer Fe-amorphous coatings were successfully deposited on high strength low alloyed (HSLA) steel, which is a representative structural material for offshore construction. The single-layer coating showed continuous corrosion and the multi-layer coating showed delamination induced by Al-3%Ti bond coat galvanic corrosion. The Vickers hardness of the coating was retained after the long-term salt solution immersion test, thus, the feasibility of single-layer Fe-amorphous coating was confirmed.